Instructor Feedback and its impact on L2 Engineering Students’ Revisions - Zailin Shah Yusoff; Nuraihan Mat Daud (Development in Language Studies, 2021)
The objective of this case study is to examine the use of instructor feedback in L2 learners’ revision of their engineering reports. Seventeen third year engineering students at a university in Malaysia participated in this study. Instructor feedback and students’ revisions in their first and final drafts were the primary data collection instruments. Content analysis was used to analyze the written work. Findings highlighted that most of the instructor feedback triggered students’ revisions, which consequently resulted in significant writing improvements in the students’ final drafts. Two major recommendations of this study are: one, a structured collaborative supervision between writing instructors and the engineering faculties can reap positive results in students’ writing development. Two, wiki can be efficiently used as a feedback-revision tool for the implementation of a structured collaborative supervision.